UPAYA PENINGKATAN KETERAMPILAN RENANG GAYA DADA MENGGUNAKAN METODE DRILL BERVARIASI PADA ATLET BEGINNER TIRTA SANI GEMILANG SWIMMING CLUB - Muhammad Damarjati; Surya Adi Saputra (Jayabama: Jurnal Peminat Olahraga, 2024)
Based on observations in the field of Tirta Sani Gemilang Swimming Club (TSG SC) athletes, their breaststroke swimming skills are still said to not meet the breaststroke skill indicators, therefore the aim of this research is to improve breaststroke swimming skills using varied drill methods in beginner athletes. TSG SC achievements. This research is sports action research (PTO) using qualitative descriptive and quantitative descriptive methods. This research used 3 cycles with 3 meetings each cycle. The subjects of this research were TSG SC beginner athletes aged 11-13 years, totaling 14 athletes. From the research results, various drill methods can be very effective in improving breaststroke swimming skills. The assessment was carried out at the end of the cycle, the results in cycle 1 were body position 41.67%, arm movement 38.10%, leg movement 38.10%, breath taking 67.86% then in cycle 2 body position 61.91%, arm movement 54.76%, leg movement 57.14%, breath taking 89.29% then in cycle 3 body position 91.67%, arm movement 83.33%, leg movement 85.71%, breath taking 100%. The conclusion from the results of this study shows that the use of various drill methods is effective in improving breaststroke swimming skills in novice athletes aged 11-13 years at TSG SC